FINANCIAL THE EFFECT OF ADVERSITY QUOTIENT AND NEED FOR ACHIEVEMENT TOWARD ENTREPRENEURIAL INTENTION - Askalania, Kamilah; Purwana, Dedi; Fidhyallah, Nadya Fadillah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
The research, entitled The Effect of Adversity Quotient and Need for Achievement on Entrepreneurial Intentions, aims to find out how the influence of Adversity Quotient and Need for Achievement on Entrepreneurial Intentions of Students of the Faculty of Economics, State University of Jakarta batch 2018 with a sample of 200 students. The research method uses quantitative research with multiple regression analysis and data collection techniques carried out online through questionnaires. The results of the study revealed that the Adversity Quotient had a significant effect on entrepreneurial intentions with a t-test value of 5.021 > ttable 1.621. Second, Need for Achievement has a significant effect on entrepreneurial intentions with a t-test value of 2.038 > ttable 1.652. Third, Adversity Quotient and Need for Achievement have a significant effect on entrepreneurial intentions with an f-test value of 20,014 > ftable 3,04.